Looming challenge of photovoltaic waste under China's solar ambition: A spatial–temporal assessment. (1st February 2022) - Wang, Chen; Feng, Kuishuang; Liu, Xi; Wang, Peng; Chen, Wei-Qiang; Li, Jiashuo
Highlights: Northern or Northwestern regions will become critical area of PV waste. We found over 80% of the total cumulative PV waste will be generated in 2040–2050. The waste volume will be almost equal to the PV inflows from 2040 onward. Silicon-based PV dominates waste market, with distinct layout from thin-film PV. The spatial–temporal features of solar waste are vital to achieve circular economy. Abstract: The challenge of when, where, and how to deal with the large volume of solar photovoltaic (PV) waste is emerging because of the continuous deployment of PV in the last 10 years. This study aimed to estimate the PV waste distribution in China from 2020 to 2050 by developing a two-step multi-criteria method combined with material flow analysis under 44 scenarios according to different PV deployment scales, growth rates and spatial downscaling criteria. The findings revealed that the total cumulative PV waste would range between 3.72E + 10 and 8.8E + 10 kg by 2050 among scenarios, over 80% of the cumulative PV waste generated in 2040–2050. The waste volume would be almost equal to the material inflows for PV installation from 2040 onward. Our results also showed an uneven PV waste distribution among regions with high concentration in the Northern or Northwestern regions, with Shandong, Hebei, Inner Mongolia or Xinjiang being the top provinces. Additionally, among different PV technologies, we found that the crystalline silicon PV waste accounted for over 50% of the total waste, and was mainly located in the Northern and Northwestern regions, whereas the thin-film PV wastes distribution was concentrated in the Eastern and Northern regions. This spatially explicit assessment of solar PV wastes distribution expands knowledge on PV waste and provides information on waste magnitude, trends, locations, and waste types toward formulating varied and refined management strategies and plans of provinces, thus shedding light on the possibility of a circular economy, and serves as an example for other large PV-utilizing countries.